A novel mutation in CELSR1 is associated with hereditary lymphedema. Issue 1 (December 2016) - Gonzalez-Garay, M.; Aldrich, M.; Rasmussen, J.; Guilliod, R.; Lapinski, P.; King, P.; Sevick-Muraca, E.
Abstract Background Biological evidence reported in the literature supports the role of CELSR1 as being essential for valvular function in murine lymphatics. Yet thus far, there have been no variants inCELSR1 associated with lymphatic dysfunction in humans. Case Presentation In this report, a rare early inactivating mutation inCELSR1 is found to be causal for non-syndromic, lower extremity lymphedema in a family across three generations. Near-infrared fluorescence lymphatic imaging shows that instead of being propelled within the lumen of well-defined lymphatic vessels, lymph moved in regions of both legs in an unusual fashion and within sheet-like structures. Conclusion CELSRI may be responsible for primary, non-syndromic lymphedema in humans.